A Mathematical Model toAssessFailure due to Longer Lead Times in SMEs in IT Sector - H, Aditya Pai; Behera, Prakash; Dash, Chimaya; Pareek, Piyush Kumar (International Journal of Computer Sciences and Engineering, 2025)
The Small and Medium Enterprises (SMEs) uses a lead time to complete the work in the estimated time period. The longer lead time is the fault in which the SMEs take longer time period to complete the work. The reason for this discussed in this paper which are termed to be as „waste‟ phenomenon. This phenomenon can be assessed using failure mode effective analysis (FMEA). The paper discusses on the causes behind the wastes using the survey and analysis of the responses from the survey. Then the failure modes identification using FMEA, followed by the mathematical model to assess the failures.